Understanding the performance of a pilot vermiculite exfoliation system through process mineralogy. (15th October 2015) - Udoudo, Ofonime; Folorunso, Olaosebikan; Dodds, Christopher; Kingman, Samuel; Ure, Alex
Highlights: Process mineralogy was applied to understand the performance of a microwave exfoliation system. The degree of vermiculite exfoliation is dependent on the mineral interlayer water content. The pure vermiculite exfoliates at a higher degree than mixed layered hydrobiotite. Abstract: This paper reports on the application of process mineralogy to understand the experimental performance of a microwave based system for the exfoliation of vermiculite type minerals. When montmorillonite type clay structures are exposed to high intensity electric fields they expand very rapidly with the degree of expansion being directly related to the applied electric field strength. This basic understanding of the interaction of microwave fields with such materials has been used to develop a pilot scale microwave based process for the exfoliation of vermiculite. During commissioning of the system it was noted that vermiculites from different geographical sources behaved very differently in terms of the achieved expansion ratio. A systematic mineralogical evaluation of these different materials was carried out using Mineral Liberation Analysis (SEM/MLA), Thermo-gravimetric analysis and X-ray Diffraction (XRD) in order to determine the reasons for the variation in performance. Samples from vermiculite mines in Australia, Brazil, China and South Africa were studied. The mineralogy and mineral characteristics such as liberation, size and texture of the samples were quantified for each ore sample. The South African and Australian samples were found to be predominantly hydrated forms of mica. The Brazilian sample was predominantly composed of vermiculite while the Chinese sample was composed almost totally of hydrobiotite. The relationships between the form of hydration and degree of expansion were derived and it is shown that pure vermiculite exfoliates at lower field intensities than the other forms of hydrated mineral. The paper concludes with deductions obtained from the mineralogical assessments of the vermiculites, thereby elucidating the reasons for the performance observed for each feed material in the microwave exfoliation system.